Effect of Leverage, Profitability and Audit Committee on Audit Delay with KAP Reputation as Moderating Variable - Agustina Dianova; Titik Mildawati; Kurnia Kurnia (Budapest International Research and Critics University, 2021)
This research is meant to find out whether the influence of stock leverage, profitability and audit committee on audit report lags with a moderating variable of Public Accounting Firm (KAP)’s reputation. The research population was mining company listed on the Indonesia Stock Exchange (IDX) in the period of 2014 to 2018. This research has been done by using purposive sampling method and applied quantitative research. The data has been obtained from www.idx.co.id. The samples are 69 companies. The independent variables leverage, profitability and audit committee. The dependent variable is audit delay. Moderating variable is KAP’s reputation. This research has been done by using multiple linear regressions and statistics. Based on the result of the research, it indicates that leverage and profitability does not give any influence to the audit delay. KAP’s reputation does not moderate the effect of leverage, profitability and audit committee on audit delay audit committee gives negative influence on audit delay.